Evaluating Trends in Interior Design Strategies and Their Impact on the Emotional Experience of Older Adults - Lintong Li; Suhua Wang; Noranita Mansor; Athira Azmi; Jialing Xiang (Buildings)
With the intensification of global population aging, attention to the emotional health of the elderly continues to grow. Traditional interior architectural design primarily focuses on optimizing physical functionality; however, this approach is no longer sufficient to meet the increasingly complex emotional needs of the elderly. Integrating the Three-Level Theory of Emotional Design (TTED) into interior design provides a significant opportunity to systematically address the multidimensional needs of the elderly. However, existing research is often fragmented and lacks thematic literature reviews to summarize the key factors, characteristics, and design strategy frameworks of interior design. This study aims to evaluate the impact of interior design on the emotional experiences of the elderly and to construct a conceptual framework to address current research gaps. By establishing rigorous selection criteria, 39 high-quality studies were identified from the Scopus, Web of Science, and Mendeley databases. Using ATLAS.ti 9 for thematic analysis, five core themes were distilled: aesthetics, use and function, emotional reflection, design strategies, and emotional experience. The findings revealed that architectural interior design practices often paid limited attention to the emotional needs of older adults. Through a comprehensive literature review, 10 key design features were identified, including multi-sensory attributes, morphological characteristics, cultural elements, and natural components, alongside 17 related research directions. The study introduces a dynamic feedback mechanism within the framework of the proposed architectural interior design strategy, highlighting the importance of employing multiple strategies that balance and complement each other in practical applications. Additionally, the study clarifies future research directions, offering theoretical support and practical guidance for designers to address the complex needs of the elderly. This achievement provides a systematic reference for the future development of interior architectural design and has significant implications for improving the emotional experience of the elderly.